1958
DOI: 10.1136/bmj.2.5109.1377
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Infection Resistant to Chloramphenicol, Erythromycin, and Novobiocin

Abstract: To the Nuffield Foundation we are particularly indebted; they, by financial ,ssistancc, not only ensured the development of the apparatus but also ils clinical success by their support to the project as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

1960
1960
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…This finding has also been reported by F in l a n d (29,30). The lack o f resistance when the erythromycin novobiocin regimen was used was in keeping with the results o f B a r b e r et al (26).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This finding has also been reported by F in l a n d (29,30). The lack o f resistance when the erythromycin novobiocin regimen was used was in keeping with the results o f B a r b e r et al (26).…”
Section: Discussionsupporting
confidence: 73%
“…Results in children also appear to have been better, perhaps because o f the age or the nature o f the underlying health o f the patient (23). In several studies, however, the problem o f erythromycin resistance was underscored and confirmed our experience that resistant strains implanted readily and in addition, resistance could develop in a given phage type o f organism while the drug was being given (24)(25)(26). Data on the use o f chloramphenicol as the sole agent in staphylococcal disease are not extensive (27) but A bboud and W a is b r e n 's data, as well as those from the Mayo Clinic (14) were similar to ours.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Degrees of cross-resistance between chloramphenicol and the chemically-unrelated chlortetracycline have been described in respect of Staphylococcus pyogenes and E. coli by P ansy et al [1950], while Barber et al [1958] have reported a moderate increase in resistance to chloramphenicol in staphylococci made resistant to the unrelated erythromycin. From tables III and IV it is possible to demonstrate a strongly unilateral cross-resistance involving chloramphenicol and oxytetracycline.…”
Section: Discussionmentioning
confidence: 99%